2007
DOI: 10.1177/0092055x0703500105
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Exams: The Impact of Two-Stage Cooperative Tests

Abstract: Decades of research have documented the positive impacts of cooperative learning on student success: increased learning, retention through graduation, improved critical thinking, and intrinsic motivation. One cooperative teaching technique, however, has received relatively little attention. In the two-stage cooperative, group, or “pyramid” exam students first take an exam individually—as in traditional testing—and then take the same exam together with their learning group, with the exam grade being a weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 14 publications
6
66
0
1
Order By: Relevance
“…This finding has also been reported by others [4], [5]. Others have argued that two-stage exams increase student enjoyment [5], reduce student anxiety [6], and more closely link the process of testing with the process of learning [7].…”
Section: Introductionsupporting
confidence: 81%
“…This finding has also been reported by others [4], [5]. Others have argued that two-stage exams increase student enjoyment [5], reduce student anxiety [6], and more closely link the process of testing with the process of learning [7].…”
Section: Introductionsupporting
confidence: 81%
“…Only a few studies have attempted to measure the benefits of two-stage exams on learning in science: In a recent study, Gilley and Clarkston (2014) reported knowledge gains (increases in student learning, i.e., the original acquisition of knowledge by students) due to the collaborative part of the exam in a science course on natural disasters, whereas other studies in biology (Leight et al, 2012) and physiology (Cortright et al, 2003) have focused on the retention of content. A positive impact on student motivation, reduced test anxiety, increased collaborative skills, and improved perception of the course were also mentioned in a number of other studies (see references in Gilley & Clarkston, 2014;Leight et al, 2012;Zipp, 2007). Potential limitations of two-stage exams are a reduced number of questions on the tests (to make time for the group portion) and a slightly higher administrative effort.…”
mentioning
confidence: 83%
“…Collaborative tests have been used for some time in a variety of formats (see summaries in Leight, Saunders, Calkins, & Withers, 2012;Zipp, 2007). The two-stage format discussed in this article (sometimes referred to as group test Cortright, Collins, Rodenbaugh, & DiCarlo, 2003;or pyramid exam, Cohen & Henle, 1995) has also been used in the past, in particular in team-based learning as part of the readiness assurance process (see e.g., http//:www.teambasedlearning.org).…”
mentioning
confidence: 99%
“…An alternative to this traditional format is the collaborative test, in which students work together in small groups to answer test questions. In the two-stage exam, perhaps the most common method of collaborative testing, students independently complete a test and then immediately complete the same, or similar, test again in groups of four; a proportion of each student's grade is assigned to the independent-and group-test sections (Cortright, Collins, Rodenbaugh, & DiCarlo, 2003;Stearns, 1996;Yuretich, Khan, Leckie, & Clement, 2001; see Leight, Saunders, Calkins, &Withers, 2012, andZipp, 2007, for summaries of select collaborative testing literature). For recommendations on the use of two-stage exams in the classroom, see Appendix 1 (available at http://www.nsta.org/college/ connections.aspx).…”
mentioning
confidence: 99%